Concept mapping as a tool to engage a community in health disparity identification. - Risisky, Debra; Hogan, Vijaya K; Kane, Mary; Burt, Beneta; Dove, Cassandra; Payton, Marinelle (Ethnicity & disease, 2008)
Objectives: To engage a community to critically examine local health disparities. Design: Concept mapping is a tool used to rapidly assess the variations in thinking of large stakeholder groups' about a particular topic. Setting: Jackson, Mississippi. Participants: Community members. Methods: Dialog groups and community meetings were held, and participants were asked to respond to the statement, "A specific thing that causes African Americans to get sicker and die sooner is⋯" Aggregate responses were rated for importance and feasibility and then sorted into related groups. Aggregate sorts and ratings were then processed by using multidimensional scaling and hierarchical cluster analysis. Results: There were 132 (unduplicated) reported contributors to health disparities. These responses fell into eight general clusters: economic issues, government, contextual factors, cultural factors, HIV, stress, environment, and motivation. Factors respondents felt were the most important contributors to disparities (economic factors, contextual factors, stress) did not correlate with those that they thought were most likely to be changed in society (contextual factors, government, motivation). Conclusions: Concept mapping provided a mechanism for rapidly documenting community thinking about health disparities. This mechanism stimulated community dialog and was used as a first step toward the long-term goal of creating equal community, academic, and medical partnerships for addressing disparities. The concept mapping process stimulated critical thinking about contributors to health inequities and uncovered contextual factors previously unknown to researchers and public health planners. The process allowed for active engagement and exchange of knowledge between the community and researchers and allowed a mechanism for identifying and rectifying disconnects in knowledge within and between stakeholder groups.
Keywords: *Community Participation; *Concept Formation; *Health Status Disparities; Adult; African American; African Americans; Aged; Community dialog; Concept Formation; Concept mapping; Consumer Participation; Female; Health Status Disparities; Health disparities; Humans; Jackson; Male; Middle Aged; Mississippi; United States; adult; aged; article; cluster analysis; concept formation; concept mapping; consumer; critical thinking; cultural factor; dept.pch; economics; feasibility study; female; goal attainment; government; health care planning; health status; human; male; medical research; middle aged; motivation; professional practice; public health; scale up; stress; ⛔ No DOI found

Pharmacist conscience clauses and access to oral contraceptives - Flynn, D. P. (Journal of Medical Ethics, 2008)
The introduction of conscience clauses after the 1973 US Supreme Court decision in Roe v. Wade allowed physicians and nurses to opt out of medical procedures, particularly abortions, to which they were morally opposed. In recent years pharmacists have requested the same consideration with regard to dispensing some medicines. This paper examines the pharmacists' role and their professional and moral obligations to patients in the light of recent refusals by pharmacists to dispense oral contraceptives. A review of John Rawls's concepts of the “original position” and the “veil of ignorance”, along with consideration of the concept of compartmentalisation, are used to assess pharmacists' requests and the moral and legal rights of patients to have their prescriptive needs met.
Keywords: *Continuity of Patient Care/st [Standards]; *Contraceptives, Oral/sd [Supply & Distribution]; *Moral Obligations; *Pharmaceutical Services/es [Ethics]; *Pharmacists/es [Ethics]; *Refusal to Treat/es [Ethics]; Continuity of Patient Care; Continuity of Patient Care/es [Ethics]; Contraceptives, Oral; Female; Humans; Moral Obligations; Pharmaceutical Services; Pharmaceutical Services/lj [Legislation & Jurisprudence]; Pharmacists; Refusal to Treat; Refusal to Treat/lj [Legislation & Jurisprudence]; Religion; dept.pch; ethics; female; human; legal aspect; morality; oral contraceptive agent; patient abandonment; patient care; pharmacist; pharmacy; religion; review; standard

Our men are grinding out: a qualitative examination of sex ratio imbalances, relationship power, and low-income African American women's health. - Bontempi, Jean M Breny; Eng, Eugenia; Quinn, Sandra Crouse (Women & Health, 2008)
In the United States, the number of HIV/AIDS cases among women of color is increasing, with African American women now comprising 60% of all female AIDS cases. Scholars have attributed this imbalance to social factors. The aim of this study was to explore the impact that relationship power has on heterosexual women's ability to practice safer sex. Five focus groups were conducted with 24 African American women, aged 18-57 years, residing in public housing in rural North Carolina over a six-month period in 2000. Findings suggest that women maintain their independence, despite inequities in relationship power and remain strong to make a better life for their families. Recommendations are made to promote and build upon this social identity that women have in order to help them practice healthier behaviors.
Keywords: *African Americans/px [Psychology]; *Cultural Characteristics; *Poverty/eh [Ethnology]; *Power, Psychological; *Sexual Behavior/eh [Ethnology]; *Women's Health/eh [Ethnology]; Adult; African American; African American women; African Americans; Anecdotes as Topic; Cultural Characteristics; Female; Focus Groups; HIV Infections; HIV Infections/eh [Ethnology]; HIV prevention; Health Knowledge, Attitudes, Practice; Human immunodeficiency virus infection; Humans; Middle Aged; North Carolina; Poverty; Power (Psychology); Qualitative research; Questionnaires; Safe Sex; Safe Sex/eh [Ethnology]; Sexual Behavior; Sexual Partners; Sexual Partners/px [Psychology]; Sexual health promotion; Surveys and Questionnaires; United States; Women's Health; adult; article; attitude to health; behavior; cultural factor; dept.pch; ethnology; female; human; information processing; literature; middle aged; poverty; psychological aspect; questionnaire; safe sex; sexual behavior; sexuality; women's health

Strategies for living long and healthy lives: Perspectives of older African/Caribbean-American women - Unson, Christine G.; Trella, Patricia M.; Chowdhury, Sutopa; Davis, Elizabeth M. (Journal of Applied Communication Research, 2008)
The influence of health and socioeconomic status on perceptions of aging and adaptation strategies of older African/Caribbean-American women was examined. Responses of 38 women (average age = 77.3 years) to: “What do you like and dislike about growing old?” and To what would you attribute your long life? were analyzed. Respondents were classified as: financially independent/healthy, financially dependent/healthy, financially independent/not healthy and financially dependent/not healthy. Narratives revealed declining health and restricted financial resources limited perceptions of opportunities for well-being. Despite differences in health and financial status, groups had some common strategies: avoiding risk behaviors, holding moral beliefs, optimism, altruism and spirituality. It was concluded that health and socioeconomic status had some influence on perceptions of aging and adaptation strategies.
Keywords: African-American; Aging perspectives; Caribbean-American; Older adult; dept.pch